The Global Transformation Toward Testing for Accountability - Smith, William C. (Education Policy Analysis Archives, 2014)
To ensure equal access to high quality education, the global expansion of universal basic education has included accountability measures in the form of academic tests. Presently the majority of countries participate in national testing; however, the past two decades have seen a substantial shift in test characteristics and aims. This article investigates the global transformation toward testing for accountability, where intentional or unintentional positive or negative consequences are applied to educators (teachers and administrators) based on their student’s test scores, in light of the emerging global culture, identified by World Culture theorists. Elements of the world culture – including the expansion of western education models, an emphasis on academic intelligence, faith in science as a rational path to truth, and the decentralization of authority to the local level – justify the establishment of testing for accountability systems. Descriptive evidence from regional and international datasets, such as PISA, PIRLS, and TIMSS, illustrate the speed at which this transformation occurs. The convergence of countries toward testing for accountability and its position as an increasingly normative policy lever is illustrated in brief vignettes from the diverse systems of Hungary, Mexico, and South Korea. As testing for accountability becomes embedded in the world culture as a legitimate tool for education reform it is less prone to critical reflection. If the potential benefits and concerns of testing for accountability, outlined in this article, are not thoughtfully evaluated this global transformation will lead to a testing culture that is internalized as normative and adopted as individual values.